Optimalisasi Pemanfaatan Media Pembelajaran Berbasis TikTok sebagai Upaya Meningkatkan Hasil Belajar Siswa - Simanjuntak, Hana Elisabet; Purba, Hasna Cecilia; Ginting, Jesika Trimanda; Putri A. Aruan; Panjaitan, Ribka Joy Nejevrina; Rini Herliani (Indo-MathEdu Intellectuals Journal, 2024)
As technology evolves, social media platforms like TikTok have started to be utilized in education as interactive and engaging tools. The aim of this research is to explore the potential of TikTok as a learning medium to improve student learning outcomes. This study uses a literature review method to analyze various sources related to the use of TikTok in education. Data were collected from five academic journal articles and literature reviews that discuss the use of TikTok in different educational contexts. The data analysis technique used in this study is content analysis, which identifies key themes from the related articles and examines the relationship between TikTok usage and student learning outcomes. The research results show that TikTok can enhance student engagement and motivation in learning and have a positive impact on their learning outcomes. TikTok has the ability to present educational material innovatively and effectively by utilizing an appealing visual format. If used correctly, TikTok can become a valuable learning medium. Thus, TikTok offers teachers the opportunity to create more creative and engaging lessons.